2023
DOI: 10.3390/molecules28041856
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Sulfur-Containing Heterocyclic Analogs Induce Sub-G1 Arrest and Apoptotic Cell Death of Laryngeal Carcinoma In Vitro

Abstract: In this study, we speculate that the hydroxyl-containing benzo[b]thiophene analogs, 1-(3-hydroxybenzo[b]thiophen-2-yl) ethanone (BP) and 1-(3-hydroxybenzo[b]thiophen-2-yl) propan-1-one hydrate (EP), might possess antiproliferative activity against cancer cells. Hydroxyl-containing BP and EP show selectivity towards laryngeal cancer cells (HEp2), with IC50 values of 27.02 ± 1.23 and 35.26 ± 2.15 µM, respectively. The hydroxyl group present in the third position is responsible for the anticancer activity and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…As extracellular ROS can induce apoptosis (Zhang et al, 2015), the degree of apoptosis reflects ROS-induced cytotoxicity. The fluorescence results shown by the apoptosis kit observed a decrease in the number of green + cells after FE intervention (Figure 2E), and for more accurate quantification, flow cytometry analyzed the Sub-G1 peaks, which reflected the proportion of apoptotic cells (Haridevamuthu et al, 2023). The results showed that L-, H-and M-FE all reduced apoptosis caused by high ROS (Figure 2F).…”
Section: Fe Protects Hacat Cells From Rosinduced Damagementioning
confidence: 90%
“…As extracellular ROS can induce apoptosis (Zhang et al, 2015), the degree of apoptosis reflects ROS-induced cytotoxicity. The fluorescence results shown by the apoptosis kit observed a decrease in the number of green + cells after FE intervention (Figure 2E), and for more accurate quantification, flow cytometry analyzed the Sub-G1 peaks, which reflected the proportion of apoptotic cells (Haridevamuthu et al, 2023). The results showed that L-, H-and M-FE all reduced apoptosis caused by high ROS (Figure 2F).…”
Section: Fe Protects Hacat Cells From Rosinduced Damagementioning
confidence: 90%
“…Sulfur-containing compounds can also be isolated from plants, and used for their diverse biological activities, such as anti-inflammatory, antioxidant, and anticancer activities [ 202 , 203 , 204 , 205 , 206 , 207 , 208 ].…”
Section: Natural Products From Plants Used In Medical Devicesmentioning
confidence: 99%